Association between polymorphisms in the promoter region of miR‐17‐92 cluster and systemic lupus erythematosus in a Chinese population. Issue 8 (16th May 2018) - Wang, Rong; Wang, Chun‐Fang; Qin, Hai‐Mei; Lu, Yu‐Lan; Wei, Gui‐Jiang; Huang, Hua‐Tuo; Xiang, Yang; Wang, Jun‐Li; Lan, Yan; Wei, Ye‐Sheng
Abstract: The aim of this study was to investigate the association of genetic polymorphisms in the promoter region of miR‐17‐92 with systemic lupus erythematosus (SLE). The gene polymorphism was analysed using SNaPshot in 312 SLE patients and 396 controls. Relative expression of miR‐17‐92 was measured by quantitative real‐time PCR. Association was found between rs9515692 and a decreased risk of SLE (CT vs CC: OR = 0.65, 95%CI, 0.46‐0.92, P = .014; CT+TT vs CC: OR = 0.64, 95%CI, 0.46‐0.90, P = .009; T vs C: OR = 0.69, 95%CI, 0.52‐0.92, P = .010, respectively). Haplotype analysis showed that C‐G‐G, C‐A‐A haplotypes were associated with an increased SLE risk (OR=4.46, 95%CI, 2.17‐9.17, P < 0.001; OR=2.33, 95%CI, 1.44‐3.76, P < 0.001, respectively). T allele and CT+TT genotypes in rs9515692 were associated with decreased risk of anti‐dsDNA in SLE (CT+TT vs CC: OR = 0.42, 95%CI = 0.24‐0.72, P = .002; T vs A: OR = 0.49, 95%CI = 0.31‐0.79, P = .003). Moreover, rs9515692 CT+TT genotypes had a higher level of miR‐17 as compared to CC genotype ( P = .017). These findings suggest that the rs9515692 CT+TT genotypes were a protective factor for the susceptibility of SLE, probably by increasing the expression of miR‐17.